(untitled) (Bangladesh Journal of Neuroscience, 2013)
Background: Stroke is the third commonest cause of death in developed countries and is responsible for the physical disability of a large population. The study was designed to see the association of serum folic acid with ischemic stroke. It was concluded that the low levels of folic acid are associated with ischemic stroke. Aim and objectives: To evaluate the association of serum folic acid level with ischemic stroke and to measure and compare the serum folic acid level among the cases and control subjects. Material and method: This study was a case-control study which was conducted in the Department of Neurology and Department of Biochemistry of BSMMU, Dhaka, between the period of 1st January 2010 and 31st December 2011 for duration of two years. A total number of 60 patients presented with ischemic stroke and 60 control person were enrolled in this study. All patients of both sexes, aged between 20 years and above presented with ischemic stroke, from 0 day to 1 month that was confirmed by CT scan of head/MRI of brain. Blood sample was collected from the cases and the controls and analyzed at the Dept. of Biochemistry, BSMMU for estimation of serum folic acid, serum homocysteine fasting blood sugar. Fasting lipid profile for cases only. Result: The mean ± SD of age of the cases was 58.42 ± 11.47 and among the cases 45 (75.0%) were male and 15 (25.0%) were female. Among the control male and female were 43 (71.7%) and 17 (28.3%) respectively. The mean (±SD) serum folate level of case and control group was 6.26(± 4.06) and 8.07(± 4.70) respectively. Statistically significant differences was observed between case and control group in term of Serum folate (p<0.05). This study showed serum folate level was deficient at the early period of ischemic stroke. Conclusion: Low serum folate concentration is significantly and independently associated with increased risk for ischemic stroke. DOI: http://dx.doi.org/10.3329/bjn.v28i2.17173 Bangladesh Journal of Neuroscience 2012; Vol. 28 (2): 74-80